Peningkatan Kapasitas dan Mutu Produk Brownies Tempe di Industri Rumah Tangga (IRT) “Browniesta” melalui Introduksi Teknologi Tepat Guna - Dwi Ishartani; Windi Atmaka; Lia Umi Khasanah; Setyaningrum Ariviani; Siswanti Siswanti (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
Tempeh had been recognized worldwide as a superfood. In Pengkok Village, Kedawung Sub-district, Sragen Regency, there were several traditional tempeh producers which supply fresh tempeh around Kedawung Sub-district. Tempeh produced in this area was also used as raw material for brownies production.